FRUIT AND SEED DEVELOPMENT OF FIVE VARIETIES OF HUSK TOMATO IN SINALOA - Rodríguez-Burgos, Alejo; Ayala-Garay, Oscar Javier; Hernández Livera, Adrián; Leal-León, Víctor Manuel; Cortez-Mondaca, Edgardo (Revista Mexicana de Ciencias Agrícolas, 2018)
Husk tomato has been cultivated in Sinaloa, Mexico, for 20 years and its importance increased in the last decade. There is little systematic information of management and productive potential of different varieties. The development of fruits and seeds and its quality, was studied on five varieties (Querétaro, Rendidora, Mahone, Orizaba, Carriceño) planted on two dates (PD1: September 6th and PD2: October 16th, 2008). Querétaro and Mahone varieties had on average, the longest fruit (37 and 34 cm), wider (43 and 40 cm) and heavier (38 and 34 g) respectively, this led the Querétaro variety to a higher (53 t ha-1) fruit yield (FrutY). The best crop development was observed in PD1, because PD2 presented a severe attack of powdery mildew (Podosphaera xanhtii), obtaining a FrutY 7.5 times lower. The growth kinetics of fruit’s weight was sigmoidal and showed that the peak was reached at 35 days after flowering (AF) (38 g). There were differences in the growth kinetics of a thousand seeds weight between the two PD; while in PD1, growth was linear, meaning that the maximum was not reached at 56 AF (last sampling); in PD2, growth reached a maximum at 42 AF (1.26 g). Similarly, the germination and seed vigor (first count in germination test) peaked at 56 AF (82% and 71% respectively).
Keywords: Physalis ixocarpa Brot; planting dates; seed quality; yield